Frequency of Nontraumatic Epistaxis in Older Male Patients - Sultan, Syed Mohammed Tipu; Sattar, Md Abdus; Khan, Mahiuddin; Alam, Zahedul; Mostafa, Golam; Raquib, Ahmed (Bangladesh Journal of Otorhinolaryngology, 2020)
Introduction: Epistaxis is a common problem which may affect all age groups. It has bimodal presentation.Nontraumatic epistaxis may affect more frequently among older male. Objective: It is important to observe the common factors related with the different etiological types of epistaxis. It is also important to observe the various socio demographic characteristic of the patient with pattern of presentation of the epistaxis. Mehods: Cross-sectional study in tertiary level hospital. From July 2012 to June 2013, 176 participants were selected. Results: Traumatic epistaxis was more frequent (70.51%) among younger age group (age <45yeras), whereas non-traumatic epistaxis was more frequent (72.92%) among older age group (age >45yeras). There was a statistically significant difference between the different age group with their etiology of the epistaxis (P = <0.001). Bangladesh J Otorhinolaryngol; April 2017; 23(1): 32-40